Persepsi Wisatawan Terhadap Objek Daya Tarik Wisata Tenganan Pegringsingan, Kabupaten Karangasem - Apriani, Ni Luh; Suharsono, Naswan; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the tourist’s perceptions about Tenganan Pegringsingan tourist attraction. This type of research is a qualitative descriptive study. The population of the study is tourists visiting Tenganan Pegringsingan with an infinite number and 100 respondents were taken using incidental sampling techniques. Data were collected using a questionnaire and analyzed with descriptive analysis techniques. The results showed that tourists' perceptions of Tenganan Pegringsingan tourist attraction in terms of the dimensions of attractions, amenities and accessibility were very amenable. That means Tenganan Pegringsingan tourist attraction has a unique nature, tradition and culture. The existence of a tracking tour, a friendly community, a safe tourist attraction environment, no entrance fee (there are donations that can contribute voluntarily), supporting facilities are available and have an easy access to Tenganan Pegringsingan tourist attraction